Relationship between lean system and small medium enterprises (SMES) performance - Mohd Nor, Norasmiha (2019)
Lean system has attracted many researchers and practitioners since its remarkable achievement was broadly reported and had become a widely-research topic. It is fair to state that some research gaps still exist. This study aims to examine the status of lean system implementation and its impact on the operational performance of Small and Medium Enterprises (SMEs), thereby to develop a Lean System Performance Model (LSPM) to facilitate successful lean system implementation considering the uncertainty business environment of the manufacturing sector in Malaysia. A quantitative research methodology with a survey method was employed to achieve the aim of this study. The target respondents were managerial level as they have more information related to the company and knowledge of continuous improvement strategy such as lean system. The combination of socio-technical system theory and contingency theory underpinned the relationship between lean system, operational performance and business environment. The Structural Equation Modelling (SEM) using SmartPLS software was applied to verify the research framework drawing on a sample of 210 SMEs operating in Malaysia manufacturing industry. The SEM analysis proved hard and soft lean practices have a significant impact on operational performance as measured by cost, quality, delivery and flexibility. Further analysis revealed the synergy effect between hard and soft lean practices predicting higher operational performance, in term of cost, quality, delivery and flexibility indicator. Thus, it is recommended that SMEs should consider applying soft and hard practices simultaneously rather than focusing on the specific lean practices. Robustness test confirmed the uncertainty business environment, such as competitive intensity moderates the relationship between lean system and operational performance. This study offers a new understanding of the effect on business environment and suggests SMEs should be aware of threat from the uncertainty business environment during lean system implementation.